Perancangan Model Bisnis Pelabuhan Menggunakan Typology Miles and Snow - Renatha Hutajulu; Mariana Simanjuntak (Pusat Riset dan Inovasi Nasional, 2024)
Business model design is a strategy for creating, delivering and capturing value so that companies can compete in the business environment. The port as an important point that allows business, services, and trade to take place has a changeable environment. The research aims to identify environmental factors that affect the port's business model, and provide strategy recommendations based on Miles and Snow's typology strategy analysis. Data analysis techniques using RBV, SWOT and Miles and Snow typology. The results of RBV analysis show that the port has 50% sustainable resources, 40% temporarily competitive and 10% less competitive. The results of SWOT analysis, the ports of Balige and Ajibata are in quadrant I position and it is recommended to use strategies based on the strength-opportunity matrix. The existing alternative strategies are analyzed using the Miles and Snow typology, obtaining three types of strategies that can be used, namely prospector, defender and analyzer. The strategy is expected to increase the port's competitiveness, operational efficiency and flexibility in the face of environmental changes.